Phenomenology of bipolar disorder not otherwise specified in youth: a comparison of clinical characteristics across the spectrum of manic symptoms. (25th March 2013) - Hafeman, Danella; Axelson, David; Demeter, Christine; Findling, Robert L; Fristad, Mary A; Kowatch, Robert A; Youngstrom, Eric A; Horwitz, Sarah McCue; Arnold, L Eugene; Frazier, Thomas W; Ryan, Neal; Gill, Mary Kay; et al.
<x xml:space="preserve">Abstract</x> Objectives Controversy surrounds the diagnostic categorization of children with episodic moods that cause impairment, but do not meet DSM‐IV criteria for bipolar I (BD‐I) or bipolar II (BD‐II) disorder. This study aimed to characterize the degree to which these children, who meet criteria for bipolar disorder not otherwise specified (BD‐NOS), are similar to those with full syndromal BD, versus those with no bipolar spectrum diagnosis (no BSD). Methods Children aged 6–12 years were recruited from nine outpatient clinics, preferentially selected for higher scores on a 10‐item screen for manic symptoms. Interviews with the children and their primary caregivers assessed a wide array of clinical variables, as well as family history. Results A total of 707 children [mean ± standard deviation (SD) 9.4 ± 1.9 years old] were evaluated at baseline, and were diagnosed with BD‐I (n = 71), BD‐II (n = 3), BD‐NOS (including cyclothymia; n = 88), or no BSD (n = 545). Compared to BD‐I, the BD‐NOS group had less severe past functional impairment. However, current symptom severity and functional impairment did not differ between BD‐NOS and BD‐I, even though both groups were significantly more symptomatic and impaired than the no BSD group. Parental psychiatric history was similar for the BD‐NOS and BD‐I groups, and both were more likely than the no BSD group to have a parent with a history of mania. Rates of elated mood did not differ between BD‐NOS and BD‐I youth. Conclusions Children with BD‐NOS and BD‐I are quite similar, but different from the no BSD group, on many phenomenological measures. These findings support the hypothesis that BD‐NOS is on the same spectrum as BD‐I.